Nasopharyngeal carcinoma with dural metastasis masquerading as meningioma / Nur Saadah Mohamad and Ramiza Ramza Ramli - Mohamad, Nur Saadah; Ramli, Ramiza Ramza (Faculty of Medicine, 2022)
Nasopharyngeal carcinoma (NPC) is one of the commonest head and neck malignancies in South East Asia. The tumor arises from epithelial layer of the nasopharynx, found most frequently at the Fossa of Rosenmuller (FOR). NPC can spread to its adjacent structures and cause distant metastasis. However, the occurrence of dura metastasis is uncommon despite being closely located. Consequently, a lesion of the dura may be misdiagnosed as meningioma, especially when it presents with a dural tail sign in the Magnetic Resonance Image (MRI). We reported a case of a 48-year-old lady with progressive right eye diplopia and blurry of vision which later on MRI noted an extensive base of skull mass at the petroclival, suprasellar and orbital apex with a dural tail Meningioma was the primary diagnosis until tissue biopsy of the nasopharynx and posterior part of inferior turbinate later revealed as nasopharyngeal carcinoma, non-keratinizing type.